Strengthening the Interaction Professor Student – A Study on Technology Investment Inflows in Schools - MATEI, Alexandru (Journal of Research in Educational Sciences, 2020)
Education and learning raise aspirations, establish values and, finally, enrich lives. Delivered well, education - and the human capital it creates - has many benefits for economies and for society as a whole. For individuals, education promotes employment, earnings and health. It raises pride and opens new horizons. For societies, it stimulates long-term economic growth, reduces poverty, stimulates innovation, strengthens institutions, and encourages social cohesion. School without learning is a terrible waste of precious and potentially human resources. Worse, it's an injustice. Without learning, students will be imprisoned in poor and exclusionary lives, and the children who fail the most are the most needy.